ANALISIS FAKTOR RISIKO KEJADIAN PREEKLAMPSIA PADA IBU HAMIL YANG BERSALIN DI RSUD SAWERIGADING PALOPO - Mulkiyah Zul Fadhilah; Rini Fitriani; Arlina Wiyata Gama; Rahadi Arie Hartoko; Muktar Lutfi (Journal Medical Universitas muhammadiyah Makassar, 2022)
Preeclampsia is one of the most common causes of death in pregnant women in addition to bleeding and infection. The purpose of this study was to analyze the risk factors associated with the incidence of preeclampsia in pregnant women who gave birth at Sawerigading Hospital Palopo. The method used in this study is an analytical observational method with a case control approach. The population was taken from pregnant women who gave birth at Sawerigading Hospital Palopo in the period January 2019 - October 2020. The sample selected used a simple random sampling technique with a total sample of 90 samples consisting of 45 case groups and 45 control groups according to the criteria. The data were univariately analyzed, and the chi-square test was 2x2 table with a significance level of sig p 0.05 and logistic regression test. Based on the results of the analysis, it was found that the variables of maternal age during pregnancy (p=0.803), gravida status (p=1,000), history of preeclampsia in Family history (p=0.557), and chronic history (p=0.153) did not have a significant relationship with the incidence of preeclampsia in pregnant women who gave birth at Sawerigading Hospital Palopo. The most dominant risk factor for the incidence of preeclampsia in pregnant women giving birth at Sawerigading Hospital Palopo is obesity (OR 5,632).